EFFICIENT INVESTMENT ACTIVITY OF COMMERCIAL BANKS - Kakhramonova Khusnora (Western European Studies, 2024)
This thesis pays special attention to the development commercial banks by attracting investments. Also given the contribution of investments to the economy and ways to solve some problems in commercial banks today
Keywords: commercial banks; investments; investment activity